Effect of repeated preheating on color stability of three types of composite resins and a giomer: An in vitro study - Mehdi Daneshpooy; Soodabeh Kimyai; Romina Allahyari Sani (Tabriz University of Medical Sciences, 2024)
Background. This study assessed the effect of repeated preheating of three types of composite resins and a giomer on their color stability. Methods. In this in vitro study, 128 composite resin and giomer specimens with a 10-mm diameter and a 2-mm height were evaluated in eight groups (n=16) of Heliomolar microfilled, Brilliant Enamel microhybrid, and Tetric N-Ceram nanohybrid composite resins, and Beautifil II giomer used at room temperature and also after preheating of the tube in a water bath at 55‒60 °C for 40 times. After preparing the specimens, their color parameters were measured by a spectrophotometer. The specimens were immersed in a tea solution for 3 hours/day for 40 days and underwent spectrophotometric color assessment again. The color change (∆E) was calculated and analyzed by two-way ANOVA (α=0.05). Results. The effects of composite resin type (P<0.001) and preheating (P<0.001) and their interaction effect (P<0.001) were significant on ∆E. Immersion in a tea solution caused a significantly greater color change in giomer (P<0.05). The ∆E of the microfilled composite resin was significantly higher than that of nanohybrid (P=0.003) and microhybrid composite resin (P=0.004). Conclusion. Repeated preheating of giomer, microhybrid, and nanohybrid composite resin specimens to 55‒60 °C for 40 times adversely affected their color stability in the tea solution. The color change was significantly greater for giomer.